SIMBOLIC MIGRATION AND DIALECTIC OF CULTURAL IDENTITY IN THE MIGRATION PROCESS - Seixas, Renato (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2017)
Migration arises identity questions to the migrants. Understand this complex dialectic process requires analysis of the elements that constitute the cultural identy. This article examines the migrations to explore and understand the complexity of the dialectic relations that migrants experience when they find themselves in different cultural contexts. The cultural reading method has been adopted, which aims identify archetypes, mixed cultural elements and dominant elements that compound the repertoire of references to the individual and/or migrant group in order to get a deeper comprehension the net of intertextual meanings of the cultures involved in the symbolic migration process.